2020
DOI: 10.3989/scimar.04973.14a
|View full text |Cite
|
Sign up to set email alerts
|

Size overlap in intertidal decapod communities along the chilean coast

Abstract: The intertidal crustaceans on the Chilean coast are characterized by high diversity and niche specialization. The present study applied a size overlap null model for intertidal decapod communities at four different sites on the Chilean coast. The results revealed that there is a size overlap for the four sites, though body size is significantly different for each location. This means that the reported species would share their ecological niches. The results agree with the first classic environmental descriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 9 publications
4
7
0
Order By: Relevance
“…The exposed results revealed that presence of C. cinereus in sites included in the present study agree with classic literature on biogeography of this species in continental Chilean coast (2,3,7). The presence of negative binomial distribution in many of studied sites would agree with first literature descriptions for this species for rocky shores in central Chile that mentioned that this species join groups that alive under rounded rocks in intertidal zone (6), similar pattern was reported for Petrolisthes granulosus in central Chile (5), it remarks that both species can coexists along continental Chilean rocky shore (2, 5, 6, 7), nevertheless, these references did not mention density quantitative data.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The exposed results revealed that presence of C. cinereus in sites included in the present study agree with classic literature on biogeography of this species in continental Chilean coast (2,3,7). The presence of negative binomial distribution in many of studied sites would agree with first literature descriptions for this species for rocky shores in central Chile that mentioned that this species join groups that alive under rounded rocks in intertidal zone (6), similar pattern was reported for Petrolisthes granulosus in central Chile (5), it remarks that both species can coexists along continental Chilean rocky shore (2, 5, 6, 7), nevertheless, these references did not mention density quantitative data.…”
Section: Discussionsupporting
confidence: 92%
“…This pattern was reported for inland water crustaceans in Chilean Patagonia (24,26), for intertidal invertebrates in northern Patagonian coast (27), and the gastropod Echinolittorina peruviana in Antofagasta rocky shore (12). The existence of uniform distribution in four of 19 samples probably would be to interspecific interactions, probably competence with other species that share ecological niche (5,6,7).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations